Marine and coastal protected and conserved areas strategy in Brazil: Context, lessons, challenges, finance, participation, new management models, and first results. (21st October 2019) - Maretti, Cláudio C.; Leão, Adriana R.; Prates, Ana Paula; Simões, Eliane; Silva, Ricardo B.A.; Ribeiro, Kátia T.; Geluda, Leonardo; Sampaio, Manoel S.; Marques, Fernanda F.C.; Lobo, Anna C.; de Lima, Luís H.; Pacheco, Leonardo M.; et al.
Abstract: In the last two decades, Brazil has advanced significantly with the expansion and improvement of its national system of protected areas. Until recently most of the expansion was concentrated in the Amazon region (with useful lessons). It also had an uneven ecological representation of coastal and marine ecosystems, concentrated in coastal waters. Despite significant advances, the levels of funding, staff and stakeholders' engagement remain relatively low for such a vast system. Within the past few years, key elements of a new strategy for protection of coastal and marine areas have started to emerge, combined with some participatory processes and a focus on expansion of the total area protected (from <1.5% protection of the country's marine area). These included: a renewed focus on priority areas for conservation; attention to national and international commitments and targets; clarity about the need for partnerships and funding; better engagement of Brazilian society and stakeholders; new, and more collaborative, models of protected areas management and conservation; and openness in the relationships with wider society. Significant results of this effort have started to appear: new large mosaics of oceanic protected areas were created; Amazon mangroves were recognized by the Ramsar Convention; new mangrove protected areas were created, besides other ones proposed; project proposals are under development with partners for better funding and sharing of responsibility; and there is a better engagement with stakeholders. The building of the Brazilian Blue Initiative is underway. The implementation of the proposed 15‐year marine strategy is at its onset: partnerships need to be strengthened and substantial funding is required. It will only be possible to manage the larger system of protected areas if there are more collaborative and innovative models for protected areas and conservation management. These should include partnerships with civil society, local and traditional communities and the private sector, as well as greater engagement of scientists and research institutions, stronger and more qualified tourism, volunteer work, etc. Further innovative funding mechanisms will also be needed along the way.